The affective right to the city - Duff, Cameron (2017)
This paper investigates the affective and performative aspects of the right to the city with a focus on the materialisation of this right, its corporeal coming into being. In elaborating the idea of an affective right to the city, I will refer to Judith Butler's performative theory of assembly, along with findings drawn from ethnographic research conducted among individuals experiencing homelessness in Melbourne, Australia. My research suggests that the materialisation of the right to the city is embodied in the social, material and affective occupation of urban spaces. This work reveals how the body's inhabitation of place, and the affordances of the material environment, mediate the performative expression of the right to the city. It also calls for a shift from a juridical conception of the right to the city to an affective one, more accommodating of the social and material contexts in which this right is enacted. I conclude with a brief discussion of the implications of this affective conception of rights for performative studies of homelessness in urban space.